Fuel management and handling. (ICE Publishing, 1995)
This work covers the tremendous advances in fuel handling and fuel management and their impact in increasing reactor availability. Topics covered include: fuel handling safety cases and supporting data, fuel handling equipment and facilities, sodium-cooled reactor handling equipment, failed fuel detection and repair, fuel management methods, applications and optimisation, plutonium strategies and technologies, storage, disposal options and facilities.